Spread of phlebotominae in temperate climates: province of Córdoba, Argentina - Visintin, Andrés Mario (2016)
We report the presence of the competent vectors of Leishmania spp., Migonemyia migonei and Evandromyia cortelezzii-sallesi complex south of its known distribution in the central temperate region of Argentina, in Cordoba province. The persistence of phlebotomine in the northern border of the province, its association with a case of cutaneous leishmaniasis, and the new record in the outskirts of Cordoba city, the second more populated of the country, strength the need of regular vector surveillance and a case detection sensitive health system in vulnerable regions even in temperate climates.